Pengaruh Volatilitas Arus Kas, Volatilitas Penjualan, Dan Perbedaan Laba Akuntansi Dengan Laba Fiskal Terhadap Persistensi Laba - Doli Andi; Mia Angelina Setiawan (Universitas Negeri Padang, 2020)
This study aimed to examine the effect of the volatility of cash flows, sales volatility and differences in accounting income with taxable income of the persistence of earnings. This research is classified research causative. The population in this research is manufacturing companies listed in Indonesia Stock Exchange in 2014-2018. By using purposive sampling method, there are 42 companies as samples. The data used is secondary data obtained from www.idx.co.id. The analytical method used is a panel regression analysis. The results of this study indicate that the volatility of cash flow and significant negative effect on the persistence of earnings, while variable sales volatility and differences in accounting income to taxable income has no effect on earnings persistence.